Analisis kesalahan dalam penyelesaian soal cerita matematika materi skala peserta didik kelas v sekolah dasar - Ardiyanti, Meireza Putri; Poerwanti, Jenny Indrastoeti Siti; Kurniawan, Sandra Bayu (Universitas Sebelas Maret, 2025)
This study aims to (1) describe the form of error in the conclusion of the mathematical story of scale matter experienced by students based on Newman's theory, (2) describe factors causing the occurrence of error. This research uses a descriptive qualitative approach with a case study research design. Subjects in this study were fifth grade students at Tegalsari elementary school. Data collection techniques using written test results and interviews. Data validity testing techniques using triangulation techniques and sources. Data analysis techniques using Miles and Huberman analysis, consist of (1) data collection, (2) data reduction, (3) data presentation, and (4) conclusion drawings. Most mistakes were found in the writing of the conclusion with a presentation of 31.5%. Then the error of understanding was found at 30.5%, error of process skills at 20%, and error of reading at 10.5%. While the transformation error was the least mistake experienced by the students with the presentation of 7.4%. The factors that cause the mistakes are the understanding of the student related to the material, the understanding the student of the story and the severity of the learner in solve the story, and the training of the teacher about the story.